2020
DOI: 10.3390/ijms21207613
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Acquired Cisplatin Resistance in Ovarian Cancer Cell Lines Characterized by Enriched Metastatic Properties with Increased Twist Expression

Abstract: Ovarian cancer (OC) is the most lethal of the gynecologic cancers, and platinum-based treatment is a part of the standard first-line chemotherapy regimen. However, rapid development of acquired cisplatin resistance remains the main cause of treatment failure, and the underlying mechanism of resistance in OC treatment remains poorly understood. Faced with this problem, our aim in this study was to generate cisplatin-resistant (CisR) OC cell models in vitro and investigate the role of epithelial–mesenchymal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 126 publications
1
26
0
Order By: Relevance
“…Remarkably, the shape of attached A549 p21– cells demonstrate elongation absent in the A549 WT cells ( Figure 1G ). The morphological change is reminiscent of epithelial-mesenchymal transition, known to reduce cisplatin sensitivity ( Deng et al, 2019 ; Bahar et al, 2020 ; Brum et al, 2020 ; Chen et al, 2020 ; Siraj et al, 2020 ), which is also observed in our experiments ( Figure 1E ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Remarkably, the shape of attached A549 p21– cells demonstrate elongation absent in the A549 WT cells ( Figure 1G ). The morphological change is reminiscent of epithelial-mesenchymal transition, known to reduce cisplatin sensitivity ( Deng et al, 2019 ; Bahar et al, 2020 ; Brum et al, 2020 ; Chen et al, 2020 ; Siraj et al, 2020 ), which is also observed in our experiments ( Figure 1E ).…”
Section: Resultssupporting
confidence: 85%
“…Permanent endoplasmic reticulum stress has been shown to contribute to mechanisms of the cisplatin resistance ( Bahar et al, 2020 ; Chen et al, 2020 ). In neurons, such stress is known to be induced by thiamine deficiency ( Wang et al, 2007 ; Liu et al, 2017 ; Xu et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in their respective ATCC recommended growth supplemented with fetal bovine serum (FBS). Two CisR OC cells, OV90/CisR and SKOV3/CisR were generated by the stepwise increment of cisplatin dosing method described in our previous publication [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…To generate in vitro three–dimensional (3D) spheroidal model utilized combination of hanging drop and hydrogel scaffolds modified methods [ 27 , 84 ]. The details of generation of three dimensional (3D) spheroidal model are described in the supporting information, Supplementary materials and methods, Section S1.1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation